ONTOLOGICAL AND GNOSEOLOGICAL STATUS OF INFORMATION SOCIETY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article reveals the concept of "information society" as a step in the development of modern civilization, studied the problem of the existence of information, considered the issues of the ontological status of the information society, the theory of information society.